Practical management for productivity - Hinrichs, John R. (New York : Van Nostrand Reinhold, 1978)
As we approach the decade of the eighties in the United States, it is becoming more and more clear that the productivity of the various organizations and institutions of our society is a national concern. Problems of inflation, the energy crisis, and an adverse balance of payments which never seem to go away, highlight the dependence of our society on high levels of productivity and productivity growth for maintaining economic health. These broad-scale factors, in conjunction with increasing domestic and foreign competition, and a relative plateau in the productivity increases to be gained from new technology or capital investments, contribute to this concern over productivity.
1. Introduction -- 2. A Poker Game Incentive for Attendance -- 3. Enhancing Product Quality -- 4. Positive Reinforcement to Enhance Performance -- 5. Extending Research Findings from the Psychological Laboratory to the Field Setting -- 6. Building a Participative Management System to Enhance Product Quality -- 7. A Participative Designed Pay Plan -- 8. Turning Around a History of Labor/Management Conflict -- 10. Flexible Working Hours to Enhance Productivity and Employee Morale -- 11. Innovations to Enhance Productivity in Large-Scale Technology Projects -- 12. Job Enrichment in a Large Clerical Organization -- 13. Orthodox Job Enrichment for Changing a Management System -- 14. Conclusion.
Includes index.
Keywords: LABOR PRODUCTIVITY; MANAGEMENT